Condensation of two-dimensional harmonically confined bosons with Bessel-type interactions - Mese, A.I. (2011)
We study the ground-state configurations of few interacting bosons confined in two dimensions by anisotropic harmonic potentials. By means of variational calculations, including correlation effects, we show that the arrangement of bosons strongly depends on the strength of the repulsive interaction and the anisotropy of the confinement. We compute the condensate fraction of the system and found that by increasing the anisotropy of the potential a weaker interaction suffices to destroy the condensate and favors the emergence of a crystal-like structure. © 2011 American Physical Society.